Malaysian hypermarket retailing development and expansion - Abu Bakar Sade; Hasliza Hassan; Muhammad Sabbir Rahman (Emerald Group Publishing Limited, 2013)
Purpose – The hypermarket industry in Malaysia has created a huge momentum for modern retailing concepts. The industry has been developing impressively, and the word hypermarket seems in need of a new definition. There is an overlap of the definitions for hypermarket, supermarket and shopping mall. Thus, the purpose of this paper is to focus on recent Malaysian hypermarket retailing developments that could be used as sources for definition. A few expansion opportunities are also emphasized in this paper.